Minimum number of myosin motors accounting for shortening velocity under zero load in skeletal muscle - Fusi, Luca (J Physiol, 2016)
KEY POINTS: Myosin filament mechanosensing determines the efficiency of the contraction by adapting the number of switched ON motors to the load. Accordingly, the unloaded shortening velocity (V (0)) is already set at the end of latency relaxation (LR), ∼10 ms after the start of stimulation, when the myosin filament is still in the OFF state. Here the number of actin‐attached motors per half‐myosin filament (n) during V (0) shortening imposed either at the end of LR or at the plateau of the isometric contraction is estimated from the relation between half‐sarcomere compliance and force during the force redevelopment after shortening. The value of n decreases progressively with shortening and, during V (0) shortening starting at the end of LR, is 1–4. Reduction of n is accounted for by a constant duty ratio of 0.05 and a parallel switching OFF of motors, explaining the very low rate of ATP utilization found during unloaded shortening. ABSTRACT: The maximum velocity at which a skeletal muscle can shorten (i.e. the velocity of sliding between the myosin filament and the actin filament under zero load, V (0)) is already set at the end of the latency relaxation (LR) preceding isometric force generation, ∼10 ms after the start of electrical stimulation in frog muscle fibres at 4°C. At this time, Ca(2+)‐induced activation of the actin filament is maximal, while the myosin filament is in the OFF state characterized by most of the myosin motors lying on helical tracks on the filament surface, making them unavailable for actin binding and ATP hydrolysis. Here, the number of actin‐attached motors per half‐thick filament during V (0) shortening (n) is estimated by imposing, on tetanized single fibres from Rana esculenta (at 4°C and sarcomere length 2.15 μm), small 4 kHz oscillations and determining the relation between half‐sarcomere (hs) compliance and force during the force development following V (0) shortening. When V (0) shortening is superimposed on the maximum isometric force T (0), n decreases progressively with the increase of shortening (range 30–80 nm per hs) and, when V (0) shortening is imposed at the end of LR, n can be as low as 1–4. Reduction of n is accounted for by a constant duty ratio of the myosin motor of ∼0.05 and a parallel switching OFF of the thick filament, providing an explanation for the very low rate of ATP utilization during extended V (0) shortening.